Analysis of Weaknesses Among Second-Grade Primary School Pupils on Learning Geometry Topic - Nadzeri, Mohamad Basri (Online Journal for TVET Practitioners, 2022)
The aim of this study is to identify the weaknesses of second-grade primary school pupils in learning Geometry topic. Based on the Mathematics Standard-Based Curriculum for Primary School, the Geometry topic consists of three content standards which are three-dimensional shapes, two-dimensional shapes and problem solving. Numerous studies have found that pupils have difficulties in learning geometry and lack of basic skills in mathematics. Thus, to fulfil this aim, a questionnaire was developed and administered to 30 pupils of Kerian District Primary School and supported by interview with three primary school teachers. The questionnaire data were analyzed using the Statistical Package for Social Sciences and the results of the interviews will be analyzed using ATLAS.ti. The results of this study revealed that the second-grade primary school pupils have several misconceptions especially on understanding the concept of three-dimensional shapes. It is believed that this study will help teachers develop and provide appropriate teaching and learning aids for pupils to improve their geometry understanding.